A study on materialism, anxiety and gender differences in compulsive buying behaviors among young adults in Malaysia - Lim, Shi Yuan; Lim, Yit Han; Loh, Carmen (2023)
Compulsive buying behaviors are demonstrated among most young adults regardless of which nations they belong to. This is an issue that have developed significantly every year and should be concerned by the global. In addition, the rate of bankruptcy due to compulsive buying behaviors and prevalence of anxiety disorder has an incline number, particularly the period of implementation of Movement Control Order. Therefore, this study is interested to study the relationship between, materialism, consumer anxiety, gender differences and compulsive buying behavior. A cross-sectional design is applied to conduct the study. Judgmental sampling is used to recruit a total number of 90 respondents who aged between 18 to 26 years old, with 46 males (51.1%), and 44 females (48.9%) in Malaysia. A questionnaire consists of Material Values Scale, The Self-rating Anxiety Scale and Edwards Compulsive Buying Behaviour Scale was used to collect the necessary data. This questionnaire is spread through email and different social media platforms. The results showed that there is a significant positive relationship between materialism and compulsive buying behavior. Next, it also indicated that consumer anxiety has a significant positive relationship with compulsive buying behavior. However, the findings demonstrated that there is no significant difference in compulsive buying behavior between male and female. This study able to fill in the existing research gap. Besides, the research provides future researchers a better understanding on the issue and a direction on how to conduct research on this topic. It is also beneficial for the policy makers and marketers.